Poland's competitive position in the enlarged EU - Leon Podkaminer (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
Poland's overall competitive position in the enlarged EU has been weakening. Other new EU members, as well as the candidate countries Romania and Bulgaria have been performing better since about 2000 on both important counts: GDP growth, and employment growth. Although Poland's external competitive position, measured by the trade balance to the GDP ratio has improved, this is hardly an achievement. The trade balance has improved at the expense of rather low overall GDP growth - and the contraction in gross fixed capital formation. Weakness of overall growth combined with some improvement in foreign trade balance appears consistent with the tendencies on real wages, productivity and unit labor costs. Poland's labor productivity has grown more or less in line with labor productivity in other central European NMS. However, real wages and unit labor costs have stagnated when compared with other countries. Stagnant unit labor costs appear to have been associated with unfavorable structural change in export. Poland's share in the EU-15 market rose much more slowly than those of other NMS. Moreover, Poland's share of EU-15 market in high-tech products rose at even more lower pace. At the same time Poland was losing quality/price competition in the EU-15 markets. Average price of Poland's manufacturing exports to EU-15 rose about 10% in relation to average prices of all manufacturing imports of the EU-15 countries (the years 2002-04 over 1995-98). Prices commanded by Czech, Slovak, Romanian and Bulgarian exports increased by about 20%. Compared with most other countries considered, Poland is competing with prices rather quality - especially in the low-tech, and high-tech products.
Keywords: 330; Internationaler Wettbewerb; Polen; EU-Mitgliedschaft